MODERN METHODS OF TEACHING UZBEK LANGUAGE GRAMMAR: PROBLEMS AND SOLUTIONS (Scientific journal of the Fergana State University, 2026)
This article analyzes modern approaches, methods, and technologies used in teaching Uzbek language grammar. The aim of the study is to identify the current problems in grammar teaching and to propose effective solutions. Comparative, analytical, and practical-experimental methods were used as methodological bases. The article discusses the advantages of communicative, integrative, and interactive approaches and their roles in developing grammatical knowledge. The results show that the use of modern technologies—such as multimedia tools, online platforms, and task-based learning—significantly enhances grammatical competence. The study concludes with recommendations for implementing methodological innovations in teaching Uzbek grammar.